2015
DOI: 10.1080/13811118.2014.957451
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness and Perceived Burdensomeness among Adolescents at Elevated Suicide Risk: An Examination of the Interpersonal Theory of Suicidal Behavior

Abstract: Objective The interpersonal theory of suicidal behavior emphasizes the constructs of perceived burdensomeness, thwarted belongingness, and acquired capacity, which warrant investigation in adolescents at-risk for suicide due to interpersonal stressors. Methods This study examined one component of the interpersonal theory of suicidal behavior, “suicidal desire” (suicidal ideation), in 129 adolescents (12–15 years) recruited from a general medical emergency department who screened positive for bully victimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 39 publications
4
37
0
5
Order By: Relevance
“…One meta-analysis reported that 57% of bullying victims report symptoms of posttraumatic stress disorder (PTSD) above cut-off thresholds (Nielsen, Nielsen, Notelaers, & Einarsen, 2015). Opperman, Czyz, Gipson, and King (2015) conducted a study with adolescents who were experiencing interpersonal problems such as bully victimization, bully perpetration, and/or low interpersonal connectedness. Opperman, Czyz, Gipson, and King (2015) conducted a study with adolescents who were experiencing interpersonal problems such as bully victimization, bully perpetration, and/or low interpersonal connectedness.…”
Section: The Psychological Effects Of Bullyingmentioning
confidence: 99%
“…One meta-analysis reported that 57% of bullying victims report symptoms of posttraumatic stress disorder (PTSD) above cut-off thresholds (Nielsen, Nielsen, Notelaers, & Einarsen, 2015). Opperman, Czyz, Gipson, and King (2015) conducted a study with adolescents who were experiencing interpersonal problems such as bully victimization, bully perpetration, and/or low interpersonal connectedness. Opperman, Czyz, Gipson, and King (2015) conducted a study with adolescents who were experiencing interpersonal problems such as bully victimization, bully perpetration, and/or low interpersonal connectedness.…”
Section: The Psychological Effects Of Bullyingmentioning
confidence: 99%
“…Specifically, these authors found that higher scores on a psychotherapist-rated scale of expendability, or a sense of being unwanted and/or a burden on their families, differentiated adolescents with suicidal ideation or history of attempts from other adolescents (Woznica & Shapiro, 1990). Lastly, providing first evidence about the applicability of IPTS to an adolescent population, Opperman and colleagues reported that low sense of belongingness with family combined with high perceived burdensomeness was associated with suicidal ideation among adolescents recruited from an emergency department (Opperman, Czyz, Gipson, & King, in press). We are building on this and other existing work by testing all three IPTS components using a prospective design in a sample of acutely suicidal adolescents.…”
mentioning
confidence: 99%
“…Despite limited evidence on effective treatments for suicidality and SH in youth, recent data support the efficacy of cognitivebehavioral treatments with strong family components for reducing SA risk (Iyengar et al, 2018;Ougrin, Tranah, Stahl, Moran, & Asarnow, 2015). Integrated cognitive-behavioral therapy (I-CBT; Esposito-Smythers, Spirito, Kahler, Hunt, & Monti, 2011) for adolescents with comorbid suicidality and substance abuse was associated with a lower SA rate compared with treatment as usual (TAU).…”
mentioning
confidence: 99%
“…Dialectical Behavior Therapy (DBT) was shown to be superior to active comparator conditions in reducing SH (SAs and NSSI) in two independent studies with adolescents (McCauley et al, 2018;Mehlum et al, 2014), and in reducing SAs in one study (McCauley et al, 2018). Other treatments have been shown to reduce overall SH, suicidal ideation (SI), and overall suicidality in randomized controlled trials (RCTs) and non-randomized trials (Iyengar et al, 2018;Ougrin et al, 2015).…”
mentioning
confidence: 99%